2007
DOI: 10.1038/sj.npp.1301340
|View full text |Cite
|
Sign up to set email alerts
|

Non-Nociceptive Environmental Stress Induces Hyperalgesia, Not Analgesia, in Pain and Opioid-Experienced Rats

Abstract: It is well admitted that stress induces analgesia (SIA) via endogenous opioid release. However, there is evidence that stressful events play a role in the pathogenesis of pain, but little is known about mechanisms underlying such pain vulnerability. Previous studies reported that a single opioid exposure activates NMDA-dependent pronociceptive systems leading to long-term pain vulnerability after analgesia. Here, we studied whether prior inflammatory pain or/and opioid experiences may favour the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 48 publications
4
116
0
12
Order By: Relevance
“…Contrasting events occur in mammals experiencing acute pain versus chronic pain (Craig, 2006). Studies have shown that rats which are in chronic pain rather than acute pain express elevated pain behaviours in the presence of an aversive stimulus (Rivat et al, 2007). Children who experience the chronic stress of recurrent abdominal pain display lower levels of SIA (Dufton et al, 2007).…”
Section: The Importance Of the Type Of Noxious And Aversive Stimulimentioning
confidence: 99%
“…Contrasting events occur in mammals experiencing acute pain versus chronic pain (Craig, 2006). Studies have shown that rats which are in chronic pain rather than acute pain express elevated pain behaviours in the presence of an aversive stimulus (Rivat et al, 2007). Children who experience the chronic stress of recurrent abdominal pain display lower levels of SIA (Dufton et al, 2007).…”
Section: The Importance Of the Type Of Noxious And Aversive Stimulimentioning
confidence: 99%
“…In addition, there is indirect evidence that latent sensitization involves descending pathways. Therefore, stress is able to interrupt the suppression of hyperalgesia during latent sensitization (Rivat et al, 2007;Le Roy et al, 2011), a phenomenon that would require either triggering descending pain facilitation or stopping ongoing descending pain inhibition. The fact that antagonists of these four receptors reinstated hyperalgesia contralaterally shows that both pain sensitization and its suppression occur bilaterally in the spinal cord, which supports the involvement of descending signals.…”
Section: Physiological Mechanismsmentioning
confidence: 99%
“…Implanting chronic intrathecal catheters involves surgery, which could induce latent sensitization (Rivat et al, 2007;Campillo et al, 2011). To control for this possibility and to confirm that intrathecal NTX does not reinstate hyperalgesia in the absence of CFA-induced inflammation, we studied a control group of rats (n ϭ 8) implanted with intrathecal catheters and injected in one hindpaw with saline (50 l) instead of CFA.…”
Section: Effects Of the Mor Inverse Agonist And Mor Neutral Antagonismentioning
confidence: 99%
See 1 more Smart Citation
“…The animal's affective state may also be influenced by external circumstances. For example, environmental and social conditions modulate pain experiences in rodents (Rivat et al, 2007;Sorge et al, 2014). In humans, facial expressions can be voluntarily generated or suppressed, which can result in observer deception (Bartlett et al, 2014).…”
Section: Referencesmentioning
confidence: 99%